District cooling guide. (ASHRAE, 2013)
"Provides guidance for the major aspects of district cooling system design for inexperienced designers and offers a comprehensive reference for those immersed in the district cooling industry; also includes information on operations and maintenance and comprehensive terminology for district cooling"-- Provided by publisher.
Keywords: Air conditioning from central stations -- Handbooks, manuals, etc.; elektronické knihy; electronic books